IMPLEMENTASI SISTEM AGROFORESTRI KOPI TERHADAP KESUBURAN TANAH DAN KEANEKARAGAMAN HAYATI DI KABUPATEN BENER MERIAH DAN ACEH TENGAH - Muyassir; Teuku Firsa; Yaumil Khairiyah; Syahrul; Renaldi Safriansyah; R Ayu Chairunnisya (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Coffee-based agroforestry is a sustainable cultivation system that has the potential to enhance land productivity while maintaining ecological balance through the integration of shade trees. This study was conducted as part of the Resilient Ecological Landscape Project initiated by the Leuser International Foundation (LIF) in the Gayo Highlands, Aceh. The main objective was to establish baseline data on soil fertility and biodiversity prior to shade tree intervention, focusing on soil fertility parameters and soil macro-decomposer organisms (earthworms). The community service locations were carried out in two districts, namely Bener Meriah and Aceh Tengah, at elevations below and above 1,000 m asl, covering different soil types (Orthic Acrisols and Chromic Luvisols). A total of 60 plots were selected using purposive sampling across three land-use systems: coffee plantations with limited shade trees, coffee plantations without shade trees, and degraded or unmanaged lands. Soil fertility parameters included physical properties (texture, structure, moisture, bulk density, and solum depth), chemical properties (pH, organic carbon, cation exchange capacity, total nitrogen, available phosphorus, and macronutrients), and biological properties (microbial activity through soil respiration rate). Earthworm diversity was assessed using quadrat and hand-sorting methods by measuring species richness, abundance, and biomass at a depth of 0–30 cm. The data serve as a baseline to monitor post-intervention changes in soil quality and biodiversity, providing essential insights for sustainable coffee agroforestry management. The findings are expected to support strategies for improving coffee productivity while conserving natural resources in the Gayo region.